ENHANCEMENT OF THE DESIGNER PERFORMANCE IN KITCHEN INTERIOR DESIGN - Yazıcıoğlu, Deniz Ayşe (Advances in Social Sciences Research Journal, 2015)
The success of the interior designer is measured to the extent the interior designer meets user requirements. As such, the most important factor affecting the performance of the designer, is making evaluations for identifying users correctly and completely at the preliminary preparation stage. Interviews are made with the user at the beginning of the design process with an eye to learn the preferences, lifestyle and expectations thereof. There are several documents which will help the designer to make correct determinations at this stage. The more complete data is obtained by virtue of these documents, which in general have the nature of questionnaire, the higher performance will be achieved by the designer. The objective of the study, in this context, was determined as examination of the documents which were benefited for identifying the features of the user at the preliminary preparation stage by the designer and proposals of the designer made for necessary revisions to obtain complete and accurate data by these documents. The scope of the study is limited only to kitchen design in order to obtain detailed results. Documents related to the identification of the user as to kitchen design was researched in line with the specified scope and objective at the first stage as methodology. At the next stage, all data obtained were examined in a systematic way by comparing and the deficiencies of documents were shown. At the final stage the proposals were made to eliminate the said deficiencies. It will be possible to have the projecting process proceed more accurately and increase the designer performance by using a questionnaire to be created in line with the recommendations made within the context of the study.